Identifikasi Meloidogyne Penyebab Penyakit Umbi Bercabang pada Wortel di Dataran Tinggi Dieng - Muhamad Taher; Supramana .; Gede Suastika (Jurnal Fitopatologi Indonesia, 2012)
Branched tuber disease is a new problem on carrot cultivation in Indonesia. The disease may reduce the quantity and quality of the tubers and causing significant yield losses. Meloidogyne spp. has been identified as the primary cause of branched or forked disease of carrot in West Java. Similar disease was observed in carrot field in Dieng Plateau, Central Java. The study was conducted at three locations in the Dieng Plateau having different elevation. Nematode species identification was done by observing the perinneal pattern of 150 samples of female nematode and obtained four Meloidogyne species, namely M. arenaria, M. hapla, M. incognita, and M. javanica. All four species were found associated with branched tuber disease in three locations with M. incognita as a dominant species having prevalence levels of 50% to 58%.Key words: branched tuber disease, carrots, Meloidogyne, species identification